2000
DOI: 10.1111/1468-2354.00054
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation in Matching Markets

Abstract: Abstract:This paper develops aggregate relations for a matching market of heterogeneous suppliers and demanders. The point of departure is the analysis of two-sided matching found in Roth and Sotomayor (1990). Under particular assumptions about the distribution of preferences, the present paper derives asymptotic aggregate relations for the number of realized matches of different types in the presence of flexible contracts (such as a price). Simulation experiments demonstrate that the model also provides excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 11 publications
1
77
0
Order By: Relevance
“…The opportunity structure determines the probability that someone is able to realise his or her preferences. The choice of partner is constrained by the demographic composition of the search area and the type and number of meeting places people frequent (England & Farkas, 1986;Mare, 1991;Blossfeld & Meyer 1988;Dagsvik, 2000;Kalmijn & Flap, 2001). A literature review by Houston and colleagues (2005) shows that the marriage market metaphor is used to study the relative availability of suitable partners at the local (e.g., Ní Bhrolcháin et al, 2002), regional (e.g., Lichter et al,.…”
Section: The Marriage Marketmentioning
confidence: 99%
“…The opportunity structure determines the probability that someone is able to realise his or her preferences. The choice of partner is constrained by the demographic composition of the search area and the type and number of meeting places people frequent (England & Farkas, 1986;Mare, 1991;Blossfeld & Meyer 1988;Dagsvik, 2000;Kalmijn & Flap, 2001). A literature review by Houston and colleagues (2005) shows that the marriage market metaphor is used to study the relative availability of suitable partners at the local (e.g., Ní Bhrolcháin et al, 2002), regional (e.g., Lichter et al,.…”
Section: The Marriage Marketmentioning
confidence: 99%
“…This means of course that the estimated model only can be applied to simulate behavior conditional on the opportunity density. In Dagsvik (2000), it is suggested how an explicit equilibrium model version can be specified and how the opportunity density depends on workers' preferences and firms' technologies.…”
Section: Theoremmentioning
confidence: 99%
“…The model is based on Dagsvik (2000) where it is demonstrated that a general type of matching behavior imply, under specific assumptions about the distribution of the preferences of the women and men, a convenient expression for the corresponding marriage model.…”
mentioning
confidence: 99%
“…The literature on matching behavior does not, however, consider the aggregation problem of predicting the number of matches of each type as a function of the number of agents of each type and parameters that represent the corresponding distribution of preferences. This aggregation problem was analyzed by Dagsvik (2000) who derived a particular aggregate matching model from assumptions about the distribution of preferences of the agents in the market and assumptions about the rules of the matching behavior. The model proposed by Dagsvik (2000) offers therefore the possibility of establishing a behavioral two-sex marriage model.…”
mentioning
confidence: 99%
See 1 more Smart Citation